Respons dan Dampak Kenaikan Tarif PPN menjadi 11% terhadap Penjualan UMKM di Bangka Belitung: Studi Kualitatif - Tamara Al Ihsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this research is to examine the impact of the increase in the Value Added Tax (VAT) rate on the sales of Micro, Small, and Medium Enterprises (MSMEs), as well as to identify the perceptions and strategies of MSMEs actors regarding the Value Added Tax (VAT) rate adjustment policy. The population in this study consists of MSMEs actors in the Bangka Belitung Islands region who are affected by the Value Added Tax (VAT) rate increase. This research uses a qualitative approach and a sample selection technique with a purposive sampling. The results show that the increase in the Value Added Tax (VAT) rate has an impact on the sales performance of MSMEs.